2013
DOI: 10.1089/neu.2013.2915
|View full text |Cite
|
Sign up to set email alerts
|

Human Astrocytes Derived from Glial Restricted Progenitors Support Regeneration of the Injured Spinal Cord

Abstract: Cellular transplantation using neural stem cells and progenitors is a promising therapeutic strategy that has the potential to replace lost cells, modulate the injury environment, and create a permissive environment for the regeneration of injured host axons. Our research has focused on the use of human glial restricted progenitors (hGRP) and derived astrocytes. In the current study, we examined the morphological and phenotypic properties of hGRP prepared from the fetal central nervous system by clinically-app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 75 publications
(221 reference statements)
2
56
0
Order By: Relevance
“…The percentage of low conductance cells was the highest in VM-Ast cultures at DIV14 and decreased during maturation in VM at DIV35, while the percentages were similar in Ctx DIV14 and Ctx DIV35 (Supplemental Figure 1F). Of note, it has been shown that transplanted immature -but not mature -astrocytes exert neurotrophic support in the injured CNS (25)(26)(27)(28)(29). In addition to a wound-healing capacity superior to that in astrocytes at DIV33-35 (Supplemental Figure 1G) in a scratch injury model (28), astrocytes at DIV12-14 showed greater capacity growing on high levels of chondroitin sulfate proteoglycans (CSPGs) (Supplemental Figure 1H) in an in vitro model recreating the strongly inhibitory CSPG gradient observed in the glial scar in vivo (25).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of low conductance cells was the highest in VM-Ast cultures at DIV14 and decreased during maturation in VM at DIV35, while the percentages were similar in Ctx DIV14 and Ctx DIV35 (Supplemental Figure 1F). Of note, it has been shown that transplanted immature -but not mature -astrocytes exert neurotrophic support in the injured CNS (25)(26)(27)(28)(29). In addition to a wound-healing capacity superior to that in astrocytes at DIV33-35 (Supplemental Figure 1G) in a scratch injury model (28), astrocytes at DIV12-14 showed greater capacity growing on high levels of chondroitin sulfate proteoglycans (CSPGs) (Supplemental Figure 1H) in an in vitro model recreating the strongly inhibitory CSPG gradient observed in the glial scar in vivo (25).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, with respect to GFAP, previous studies have shown heterogeneity in both maturity and marker expression in cultures of human stem cell-derived astrocytes, but identify GFAP expression as a marker for astroglial identity (90), and GFAP is commonly used to characterize astroglial differentiation in hNSC cultures (91)(92)(93). Critically, more mature astroglial markers such as GLAST and ALDH1L1 are absent in human cell cultures ,4 wk old (90).…”
Section: Discussionmentioning
confidence: 99%
“…Such progenitors can be isolated from embryonic tissue and expanded for therapeutic applications to reduce inhibition and provide a permissive environment for neuroprotection and axonal growth (Mothe and Tator, 2013; Okano et al, 2007; Tetzlaff et al, 2011). It is therefore critical to establish efficient culture protocols for large-scale cell preparation, and characterize these cell populations in terms of their phenotypic and functional properties under different environments (Haas et al, 2012; Haas and Fischer, 2013). The present study addresses these issues by analyzing the properties of glial progenitors after long term culturing and following exposure to inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%